Analysis of clinical characteristics, prognosis and antibody pathogenicity of pemphigus patients positive for anti‐desmoglein IgG autoantibodies in remission: a retrospective cohort study. (10th November 2021) - Zhao, W.L.; Ishii, K.; Egami, S.; Xu, Z.; Funakoshi, T.; Takahashi, H.; Tanikawa, A.; Ishiko, A.; Amagai, M.; Yamagami, J.
Abstract: Background: The detection of serum anti‐desmoglein (Dsg) IgG autoantibodies has been reported to be useful for assessment of disease activity in pemphigus. However, previous studies have reported that anti‐Dsg autoantibodies remain detectable in some patients without active pemphigus lesions. Objectives: To investigate the clinical characteristics and antibody pathogenicity of pemphigus patients positive for anti‐Dsg IgG autoantibodies in remission. Methods: We retrospectively investigated pemphigus patients with a history of clinical remission who visited the Department of Dermatology of Keio University during 2019 and 2020. The antibody pathogenicity was assessed by bead aggregation assay. Results: When patients were recognized as having entered remission (PDAI = 0 and PSL ≦ 10 mg/day for 2 months), serum autoantibodies against Dsg were detected in 72 of 132 patients (54.5%, positive group; PG), but were not detected in 60 patients (45.5%, negative group; NG). Anti‐Dsg antibody titres in remission declined from the active phase in 33 patients in the PG for whom data were available. There were no differences in the chance of reducing PSL to 5 mg/day ( P = 0.885) and rate of relapse ( P = 0.279) between PG and NG, but fewer patients in PG discontinued corticosteroids ( P = 0.004). The ability of patients' sera to block aggregation of Dsg/desmocollin beads was significantly reduced in remission compared to the active phase. However, our results revealed that whole sera in remission still had pathogenic activity in seven of nine patients, and the approximately equal amounts of anti‐Dsg antibodies in active phase and remission showed similar pathogenicity. Conclusions: This study will provide guidance in cases where autoantibodies are found to be positive in pemphigus patients during remission or steroid reduction.